Organization Information Ecology and E-Commerce Adoption: Effect on Organizational SMEs Performance - Herzallah, Fadi; Mukhtar, Muriati (Journal of computer science, 2015)
Electronic Commerce (EC) has recently become the subject of interest of many researchers involved in behavioral and technology acceptance. EC was heavily studied in developed countries, but there are only a few narrowly focused studies on EC adoption in developing countries, especially in the context of Small and Medium Enterprises. A review of the literature showed that Organization Information Ecology (OIE), which is an important factor in the context of EC, has not been receiving the attention it deserves in the context of EC adoption. Based on the literature review of previous studies, a model is proposed to reviews and attempts to identify the organizational, technological and OIE factors that effect on the adoption of EC and the impact of EC on organization performance. Altogether, twelve hypotheses are proposed. The proposed conceptual model provides a foundation for test the relationships in the suggested model by using the empirical data or other techniques.